2013
DOI: 10.1002/anie.201300749
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Zinc Dihydride Stabilized by N‐Heterocyclic Carbenes

Abstract: Solubility problems solved: The first examples of discrete soluble zinc dihydride adducts with NHC ligands reacted with CO2 to produce formate species and efficiently catalyzed the dehydrocoupling of silanes with methanol. These compounds were characterized both in solution and in the solid state (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 47 publications
8
100
0
10
Order By: Relevance
“…The weak interaction is further demonstrated with the initial adduct A exhibiting elongated metal−C bonding interactions of 2.202 Å (Zn), 2.491 Å (Cd) and 2.821 Å (Hg), which are longer than the sum of covalent radii for metal−C single bonds of 1.93 Å (Zn), 2.11 Å (Cd) and 2.08 Å (Hg) . The Zn–carbene interaction is longer than in the Zn species isolated by Hillmyer and Tolman (2.04 to 2.05 Å, depending on the zinc substituents of chloride or benzyl alcohol), the zinc dihydride bridged NHC i Pr compound synthesized by Maron and Okuda (2.05 Å) as well the Zn–carbene interaction of 2.07 Å reported by Brown and Rivard . The carbene‐stabilized compounds isolated by Roesler and co‐workers yielded metal–carbene distances of 2.00 Å (Zn), 2.25 Å (Cd) and 2.18 Å (Zn).…”
Section: Resultsmentioning
confidence: 92%
“…The weak interaction is further demonstrated with the initial adduct A exhibiting elongated metal−C bonding interactions of 2.202 Å (Zn), 2.491 Å (Cd) and 2.821 Å (Hg), which are longer than the sum of covalent radii for metal−C single bonds of 1.93 Å (Zn), 2.11 Å (Cd) and 2.08 Å (Hg) . The Zn–carbene interaction is longer than in the Zn species isolated by Hillmyer and Tolman (2.04 to 2.05 Å, depending on the zinc substituents of chloride or benzyl alcohol), the zinc dihydride bridged NHC i Pr compound synthesized by Maron and Okuda (2.05 Å) as well the Zn–carbene interaction of 2.07 Å reported by Brown and Rivard . The carbene‐stabilized compounds isolated by Roesler and co‐workers yielded metal–carbene distances of 2.00 Å (Zn), 2.25 Å (Cd) and 2.18 Å (Zn).…”
Section: Resultsmentioning
confidence: 92%
“…However, the use of as toichiometric and expensive organometallic additive is as ubstantial drawback for the CO 2 transformation reaction. [47] All of these studies demonstrated the significance of the imidazolate motifs in the NHC building blocks for CO 2 activation and subsequent transformations. [46] They examined various copper/NHC catalysts using their established reaction protocol, and as eries of propiolic acids were efficiently prepared under mild reaction conditions.Areaction mechanism was proposed (Figure 7) in which the copper center activated the terminal alkyne with abase to generate acopper acetylide species and the free NHC activated CO 2 to form the NHC-CO 2 adduct.…”
Section: Methodsmentioning
confidence: 90%
“…have described [ZnH 2 (NHC)] 2 (NHC=IDipp, IMes) 9b. Interestingly, reduction of [ZnCp* 2 ] or [ZnH 2 (NHC)] 2 with H 2 at elevated temperatures gave metallic Zn 0 9b. 12 This implies that soluble zinc hydrides can undergo reductive elimination under reducing conditions.…”
Section: Resultsmentioning
confidence: 99%